Anti-bacterial activity, anti-cancer activity and nanofiber formation of certain poly (ester amides) from 2,5-pyridine dicarboxylic acid - Chitra, V.; Singh, D. Roop (Journal of Drug Delivery and Therapeutics, 2018)
A new series of four poly(ester amides) were synthesized by direct polycondensation of 2,5-pyridine dicarboxylic acid with two different varying diols and diamines in pyridine medium using diphenylchlorophosphate as a condensation agent. The two diamines employed in the synthesis were 4,4’-diamino diphenyl methane and 1,4-diamino benzene. The arylidenediols 2,5-bis(4-hydroxy-3-methoxybenzylidene)cyclopentanone and 2,6-bis(4-hydroxy-3-methoxybenzylidene) cyclohexanone were also used. The synthesized poly(ester amides) were characterized by qualitative solubility test, FT-IR, 1H and 13C-NMR spectra. The monomeric moieties were found by spectroscopic analysis to be well incorporated in the polymer back bone. The thermal phase transition behavior of the poly(ester amides) were investigated by differential thermo gravimetry (DTG). The nanofibers of synthesized poly(ester amides) with PVC and composite fibers with PVC/nanoclay were formed by electrospinning. The morphology of these composite fibers was studied by scanning electron microscopy (SEM). These poly(ester amides) were screened for their anti-bacterial potential in vitro against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Bacillus subtilis. In vitro anti-cancer activities of synthesized polymers were also evaluated against MCF7 human breast carcinoma cells. The results show that the polymers exhibited significant anti-bacterial and anti-cancer activity. Keywords: Poly (ester amides), Anti-bacterial activity, Nano fiber, Anticancer activity